Realms : the roleplaying game art of Tony Diterlizzi - DiTerlizzi, Tony; Paolini, Christopher; Lind, John. (Milwaukee, Oregon : Kitchen Sink Books an imprint of Dark Horse Comics, 2015)
New York Times bestselling creator Tony DiTerlizzi is known for his distinctive style depicting fantastical creatures, horrific monsters, and courageous heroes. His illustrations reshaped and defined the worlds of Advanced Dungeons and Dragons, Planescape, and Magic: The Gathering in the imaginations of legions of devoted roleplaying gamers during the 1990s, before he transitioned to mainstream success with The Spiderwick Chronicles and The Search for WondLa. Collected here for the first time, this book features never-before-seen artwork and photographs, in addition to showcasing DiTerlizzi's most iconic roleplaying work with commentary by the artist. Introduction by Christopher Paolini (Eragon) and featuring appreciations by Guillermo del Toro, Brom, Jane Yolen, Holly Black, Zeb Cook, Jeff Easley, and Donato Giancola, among others!
Title from cover.
Keywords: Fantasy games -- Illustrations; Role playing -- Illustrations; Illustrators -- United States